"Análise econômica do direito” e a objetivação do exercício do poder político pelo Judiciário - Santos, Bruno Calife dos (2019)
The political action of the Judiciary is a consolidated phenomenon whose origin goes back to the control of contemporary constitutionality that ended by achieving, through its exercise, a leading role beyond the limits classically considered and put to the exercise of the function of judging. From the institutional complexity that leads to new models of action to the circumstances related to the very act of interpretation, the primordial activity of the judge, with which legal Hermeneutics has been encountering in order to take an action also creative, which always comes into focus - too much of the verification of its own existence - is its degree of legitimacy, questioned, among other factors, from the lack of representativeness of its actors since they are not elected by the population in whose destination they end up influencing. The present work deals precisely with this problem in order to provide a treatment that goes beyond the critiques commonly applicable to judicial activism in order to examine the existence of a solid and coherent foundation capable of guaranteeing a dogmatic criterion for the judicial creation of law founded on objective and non-subjective elements of the decision-maker, transposed throughout its spectrum by legal pragmatism in one of its consecrates, "economic analysis of law", theoretical framework elected in function of methodological skepticism that accompanies and reinforces, in turn, by the theoretical reference set in the work of Richard Posner.